2020
DOI: 10.1029/2020gc009058
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Active Hydrothermal Vent Fields Along the Central Indian Ridge, 8–12°S

Abstract: Four new hydrothermal vent fields were discovered on the slow spreading Central Indian Ridge (8–12°S; Segments 1–3), all located off‐axis on abyssal hill structures or Ocean Core Complexes (OCCs). Each site was characterized using seafloor observation (towed camera system), plume chemistry (Fe, Mn, and CH4; Conductivity, Temperature, and Depth sensor [CTD]/Miniature Autonomous Plume Recorder [MAPR]), and rock sampling (TVgrab/dredges). Different styles of venting on each segment reflect different geological se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 62 publications
4
40
0
Order By: Relevance
“…Similarly, the locally focused melt supply on the western end of segment 30 appears to provide a moderate heat source for driving the hydrothermal circulation, although the melt supply may have decreased to a present waning state. In addition, the SDF (~9.4 km off-axis) is situated on the southern axial valley wall (Figure 7b)-this location is consistent with many vent fields that are controlled by rift-bounding faults along slow-and ultraslow-spreading ridges [10,19,21,64]. Consequently, we infer that the rift-bounding fault may be activated by the locally focused melt supply and, therefore, act as pathway for channeling hydrothermal fluids to off-axis areas [17,39].…”
Section: Hydrothermal Activity On Western End Of Segment 30supporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, the locally focused melt supply on the western end of segment 30 appears to provide a moderate heat source for driving the hydrothermal circulation, although the melt supply may have decreased to a present waning state. In addition, the SDF (~9.4 km off-axis) is situated on the southern axial valley wall (Figure 7b)-this location is consistent with many vent fields that are controlled by rift-bounding faults along slow-and ultraslow-spreading ridges [10,19,21,64]. Consequently, we infer that the rift-bounding fault may be activated by the locally focused melt supply and, therefore, act as pathway for channeling hydrothermal fluids to off-axis areas [17,39].…”
Section: Hydrothermal Activity On Western End Of Segment 30supporting
confidence: 68%
“…Sites NL04-B and WL02 are about 10.1 and 3.4 km off-axis of the eastern NTD, respectively, and surrounded by several mode-C faults (Figure 9a). Studies along the CIR (8-17 • S) have shown that diffused venting is expected to be common on fault zones of ridge flanks (up to 10 km off-axis) [10,64]. Similar to fault zones on the flanks of the Central Indian Ridge, the mode-C faults in this area may facilitate the seepage of seawater.…”
Section: Hydrothermal Activity On the Eastern Ntdmentioning
confidence: 95%
“…Like elsewhere, macrofaunal vent communities in the Indian Ocean also possess high endemicity (Ramirez-Llodra et al, 2007;Rogers et al, 2012; Figure 2). The Indian vent communities are also distinct in composition from other oceans because almost all the dominant taxa above are unique to the Indian vents (Hashimoto et al, 2001;Nakamura et al, 2012;Copley et al, 2016;Zhou et al, 2018;Kim et al, 2020). With the restricted distribution of these animals, fragmented habitat, and uncertainties about their demographic fluctuations, the proposed idea was to first place these species preemptively in the IUCN Red List of threatened species (Sigwart J. D. et al, 2019).…”
Section: Diversity and Endemicitymentioning
confidence: 99%
“…Systematic deep-sea exploration recently uncovered four new active hydrothermal vent fields in the middle region of the Central Indian Ridge (CIR) between 8 and 14 • S, where ridge morphology and tectonic structure (e.g., detachment faults and ocean core complexes, OCCs) control increased plume incidence at ridge flank and rift wall locations (Kim et al, 2020). These hydrothermal vent fields, located more than 800 km north of previously known vent fields (i.e., the Dodo and Solitaire fields, Nakamura and Takai, 2015) are characterized by particle-poor, diffuse venting with abundant vent fauna and sulfide deposition.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrothermal vent fields, located more than 800 km north of previously known vent fields (i.e., the Dodo and Solitaire fields, Nakamura and Takai, 2015) are characterized by particle-poor, diffuse venting with abundant vent fauna and sulfide deposition. Notably, these new hydrothermal vents show diverse venting styles and plume compositions, attributed to distinctive hydrothermal fluid formation conditions and transport pathways in the slow-to ultraslow-rate spreading ridge setting (Son et al, 2014;Kim et al, 2020). In particular, the Onnuri hydrothermal vent field (OVF) site, located on the summit of OCC at a water depth of ∼2,000 m in Segment 3 (Figures 1A-C), is attracting considerable scientific attention because of its isolated location, diffuse venting style, methane-rich plume composition, ultramafic-hosted system, and community of hydrothermal vent fauna.…”
Section: Introductionmentioning
confidence: 99%